2019
DOI: 10.1002/hbm.24520
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter volume covariance networks associated with dual‐task cost during walking‐while‐talking

Abstract: We studied gray matter volume covariance networks associated with normal pace walking (NPW) speed and dual‐task costs (DTCs) during walking‐while‐talking (WWT)—a mobility stress test that involves walking while reciting alternate letters of the alphabet. Using a multivariate covariance‐based analytic approach, we identified gray matter networks associated with NPW speed (mean 102.1 cm/s ±22.5 cm/s) and DTC (percent difference in gait speed between NPW and WWT, mean 25.9% ± 18.8%) in 139 older adults without de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 93 publications
(142 reference statements)
5
35
0
Order By: Relevance
“…Likewise, there is little known about the relationship between DT function and cognitive relevant brain areas. Previous studies have identified brain areas uniquely correlated with DT performance, including frontal, temporal, and cingulate regions (Doi et al 2017;Tripathi et al 2019). While not the hallmark of cognitive disorders, there is evidence of decreased volume, decrease neuronal integrity, and lower cerebral blood flow in motor-related brain areas such as the basal ganglia and primary motor cortex in those with MCI and dementia, and these findings have been shown to be associated with both single and dual task gait variability (Annweiler et al 2013;Jiji et al 2013;Nakamura et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, there is little known about the relationship between DT function and cognitive relevant brain areas. Previous studies have identified brain areas uniquely correlated with DT performance, including frontal, temporal, and cingulate regions (Doi et al 2017;Tripathi et al 2019). While not the hallmark of cognitive disorders, there is evidence of decreased volume, decrease neuronal integrity, and lower cerebral blood flow in motor-related brain areas such as the basal ganglia and primary motor cortex in those with MCI and dementia, and these findings have been shown to be associated with both single and dual task gait variability (Annweiler et al 2013;Jiji et al 2013;Nakamura et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that motor relevant brain volumes would be more associated with motor dual-task effects (mDTE), indicating a decline in motor performance under DT conditions. Based on the literature, we hypothesized that the superior frontal lobe caudate, putamen, middle parietal and cerebellum would be associated with mDTE (Allali et al 2019;Poldrack et al 2005;Tripathi et al 2019). We also hypothesized that cognitive relevant brain volumes would be more associated with cognitive dual-task effects (cogDTE), indicating a decline in cognitive performance under DT conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for a much broader implicated network in DT was also discussed in Tripathi et al (2019) . The authors hypothesize that structural brain loss in regions involved in DT, might contribute to an impaired neural functioning during DT and consequently prompt a compensation by alternative pathways.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies showed that PFC atrophies more than other regions ( Dumurgier et al, 2012 ; Storsve et al, 2014 ; Doi et al, 2017 ) and is also often functionally underutilized with age ( Holtzer et al, 2011 ). Several studies showed an association of DT performance (i.e., processing speed and executive function) and the gray matter volume of various areas of motor control including PFC ( Allali et al, 2019 ; Blumen et al, 2019 ; Tripathi et al, 2019 ). Albeit structure-function evaluations of these regions are scarce, first evidence indicates the potential moderator role, which brain prefrontal activation can have on volume loss in elderly ( Wagshul et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%